Differences in Relative Prices in the EU - Sirly Palenmark (Lund University, School of Economics and Management, Department of Economics, 2004)
Price levels differ considerably between the member states of the EU. This paper examines what causes these price differences. Disaggregated price level indexes for 13 capital cities in the EU are used in order to investigate differences in relative prices during the 1990s. It is found that such variables as physical distance, tax levels, participation in the EMU and income levels explain differences in price levels.
Keywords: E31; F41; 330; Relative prices; Purchasing Power Parity; Law of One Price